Typical Academic Electronic Library Creation - Babenko, B.O.; Babina, T.B.; Gabzovska, О.Б.; Savitsky, А.Й. (Journal of Information Technologies in Education (ITE), 2009)
In article results of electronic library applications into information space are presented. Aims, tasks, functions of typical academic electronic library are defined. Typical academic electronic library information resources are presented. Typical principles of creation, organize, storage of electronic library information resources technology are presented.